Business Process Improvement Using Quality Evaluation Framework and Root Cause Analysis at AMDK Company DC. Bali - Pramesti, Anak Agung Istri Anindya; Githa, Dwi Putra; Susila, Anak Agung Ngurah Hary (LPPM Telkom University Surabaya, 2025)
This study addresses critical inefficiencies in distribution operations at PT. AMDK Distribution Center Bali, where manual processes and system fragmentation result in document verification errors, delivery mismatches, and extended cycle times. We employed an integrated methodological framework combining the Quality Evaluation Framework (QEF) for systematic performance assessment, Root Cause Analysis (RCA) with Fault Tree Analysis (FTA) to identify underlying operational failures, and Business Process Improvement (BPI) for solution design. Process modeling was conducted using BPMN 2.0 and validated through Bizagi Modeler simulation. The QEF evaluation revealed five critical non-conforming indicators: road letter verification errors (Q6), product delivery inaccuracies (Q22), residual product inspection failures (Q23), LHPH documentation errors (Q26), and submission delays (Q28). Root cause analysis identified manual dependency, inadequate system integration, and insufficient SOPs as primary failure sources. The proposed To-Be model, incorporating automated validation, digital documentation workflows, and cross-system integration (Smartlog-SAP-OTM), achieved measurable improvements: a 17.61% time reduction in delivery operations and a 2.41% improvement in receiving processes. This research contributes a validated methodological framework for logistics process optimization in emerging market contexts, demonstrating how structured quality evaluation coupled with root cause-driven redesign can achieve sustainable operational improvements.